Hemoperitoneum secondary to spontaneous rupture of metastatic gastric leiomyosarcoma of the liver: Report of a case - Gülten KIYAK; Mehmet ÖZER; Ahmet GÜRER; Ali Önder DEVAY; Aylin YAZGAN (Turkish Journal of Gastroenterology, 2019)
-